Litigating Federalism: An Empirical Analysis of Decisions of the Belgian Constitutional Court∙. (26th May 2017) - Dalla Pellegrina, Lucia; De Mot, Jef; Faure, Michael; Garoupa, Nuno
Abstract : Belgian Constitutional Court – Conflicts between regions, communities and the central government – Allocation of competences – Decisions with high political content – Degree of political alignment between the parties in litigation and judicial behaviour at the Court – Empirical testing – All decisions of the Belgian Constitutional Court, 1985-2012 – Alignment between the alleged political preferences of the judges and the political affiliation of the Petitioner increases the rate of success of the latter